Tindak Pidana Pencurian Data Melalui Wi-Fi Perspektif Pasal 30 Ayat (3) UU Nomor 11 Tahun 2008 dan Hukum Pidana Islam - Dikri Abdul Jabar Ahmad; Muhamad Kholid; Didi Sumardi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The advancement of digital technology has transformed data into a crucial asset, while significantly increasing the threat of cybercrime, including the growing phenomenon of personal data asset theft through public Wi-Fi networks. This research examines this criminal act from two legal perpectives: Indonesian positive law through Article 30 Paragraph (3) of Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law) as amended by Law Number 1 of 2024, and Islamic criminal law (fiqh jinayah). This study aims to analyze the juridical qualifications, elements of the offense, evidentiary challenges, and compare the philosophy of punishment between the two legal systems. The research method employed is normative juridical with statutory, conceptual, comparative, and jurisprudential case study approaches. The results indicate that data thedt via Wi-Fi can be qualified as the crime of illegal access based on the elements in Article 30 paragraph (3) of the ITE Law, which constitutes a formal delict. Jurisprudence analysis reveals how judges interpret the element of “breaching a security system” in various modus operandi. From the perspective of Islamic criminal law, this act does not meet the requirements of sariqah (hudud theft) but is classified as jarimah ta’zir as it violates the principle of property protection (hifz al-mal) within the maqashid al-syariah. Data, as an intangible asset with economic value (Maliyah), receives legal protection based on contemporary ijtihad. A comparison of sanctions highlights that the ITE Law is retributive-deterrent with rigid criminal threats, whereas ta’zir in Islamic law is flexible, educative, and restorative, focusing on substantive justice and public interest. It is concluded that there is an urgent need to reform the national cyber law policy by integrating the values of flexibility and substantive justice from the philosophy of ta’zir to address the evolving dynamics of cybercrime.